REBU IN THE SPEECH NORM SYSTEM OF THE KARO COMMUNITY: CHALLENGES AND ADAPTATIONS IN THE MODERN ERA - Br Surbakti, Serli Handayani; Marsa, Yummy Jumiati (International Journal of Cultural and Social Science, 2025)
Rebu is a traditional speech norm in the Karo community that prohibits direct face-to-face communication between in-laws of opposite genders and siblings-in-law. This norm plays a crucial role in maintaining respect, social harmony, and family hierarchy. However, modernization and changing lifestyles have influenced the understanding and practice of rebu, especially among the younger generation. This study employs a qualitative phenomenological approach to explore the meanings, perceptions, and implementation of rebu within the Karo community. Data were collected through in-depth interviews with 15 informants from Naman Teran Village and validated using triangulation techniques. Findings indicate that rebu is still recognized as a vital cultural norm symbolizing respect and politeness. The younger generation generally understands the concept, though with more flexible interpretations. In young households, rebu is practiced with adaptations, such as the use of intermediaries or digital communication, to accommodate modern social contexts. Despite external influences of globalization and technology, the core values of rebu persist as a mechanism for maintaining family harmony and social order. Adaptation in practice reflects the community's efforts to balance tradition and modernity, ensuring the continuity of cultural identity.